Rivers in the sky, flooding on the ground: the role of atmospheric rivers in inland flooding in central Europe - M. Ionita; V. Nagavciuc; B. Guan (Hydrology and Earth System Sciences, 2020)
The role of large-scale atmospheric circulation and atmospheric rivers (ARs) in producing extreme flooding and heavy rainfall events in the lower part of the Rhine catchment area is examined in this study. Analysis of the largest 10 floods in the lower Rhine, between 1817 and 2015, shows that all these extreme flood peaks have been preceded up to 7 d in advance by intense moisture transport from the tropical North Atlantic basin in the form of narrow bands also known as atmospheric rivers. Most of the ARs associated with these flood events are embedded in the trailing fronts of the extratropical cyclones. The typical large-scale atmospheric circulation leading to heavy rainfall and flooding in the lower Rhine is characterized by a low pressure center south of Greenland, which migrates toward Europe, and a stable high pressure center over the northern part of Africa and the southern part of Europe and projects on the positive phase of the North Atlantic Oscillation. On the days preceding the flood peaks, lower (upper) level convergence (divergence) is observed over the analyzed region, which indicates strong vertical motions and heavy rainfall. Vertically integrated water vapor transport (IVT) exceeds 600 kg m −1 s −1 for the largest floods, marking these as very strong ARs. The results presented in this study offer new insights regarding the importance of moisture transport as a driver of extreme flooding in the lower part of the Rhine catchment area, and we show, for the first time, that ARs are a useful tool for the identification of potentially damaging floods in inland Europe.